Blue light phones as potential locations for deploying public access naloxone kits on a college campus. Issue 1 (14th February 2022) - Dworkis, Daniel A; Tang, Willis; Ritcheson, Nicolas CM; Raviv, Orian; Fowler, Andrew; Ellig, Katelin; Goley, Stephanie; Arora, Sanjay
Abstract: Objective Opioid use and the risk of opioid overdose are growing public health concerns for college-aged adults. Naloxone can temporarily reverse opioid overdoses, but only if easily accessible. On most college campuses, "blue light" phones (BLPs)—call boxes topped with a blue light—offer visible access to emergency services. We hypothesized that BLPs would provide potential naloxone access points. Participants: A major university campus in Los Angeles, CA. Methods: BLP locations were obtained using Google Maps, and the area of campus within a set distance to each BLP calculated. To model effects of loss or diversion, we simulated the random loss of various BLPs. Results: Placing naloxone kits at the 59 BLP locations could provide access within 100 m to 91.5% of the campus. With loss of half of the BLPs, campus access remained above 70%. Conclusions: Naloxone at BLP locations could be accessed from almost all campus areas.